A Survey on Important Aspects of Information Retrieval - Gupta, Y.; Saini, A.; Saxena, A.K. (Journal of Engineering and Technology (JET), 2013)
Information retrieval has become an important field of study and research under computer science due to the explosive growth of information available in the form of full text, hypertext, administrative text, directory, numeric or bibliographic text. The research work is going on various aspects of information retrieval systems so as to improve its efficiency and reliability. This paper presents a comprehensive survey discussing not only the emergence and evolution of information retrieval but also include different information retrieval models and some important aspects such as document representation, similarity measure and query expansion.